Strategic electricity planning decisions - Pereira, Sérgio (2011)
Sustainable electricity power planning involves trade-offs between multiple goals. The different attributes of each technology or generation portfolio in terms of the attainment of society goals must be assessed and included in the planning models. Optimization models always played an important role for supporting complex planning decision making, from which the particular case of the electricity industry stands out. This study addresses energy policy and strategic central decisions, presenting a long-term model for electricity planning. A MILP problem is described, which addresses a mixed hydro-thermal-wind power system close to the Portuguese electricity case. Through scenario analysis, the expected impacts in terms of costs, CO2 emissions and external energy dependence are evaluated for a 10 years planning period. Based on the assumed cost information and on the imposed technical restrictions, the obtained results put in evidence the importance of coal power plants combined with new hydro power investments for minimum cost scenarios.